Barcode ITS2: a useful tool for identifying Trachelospermum jasminoides and a good monitor for medicine market - Ning Yu (Nature Portfolio, 2017)
Abstract Trachelospermum jasminoides is commonly used in traditional Chinese medicine. However, the use of the plant’s local alternatives is frequent, causing potential clinical problems. The T. jasminoides sold in the medicine market is commonly dried and sliced, making traditional identification methods difficult. In this study, the ITS2 region was evaluated on 127 sequences representing T. jasminoides and its local alternatives according to PCR and sequencing rates, intra- and inter-specific divergences, secondary structure, and discrimination capacity. Results indicated the 100% success rates of PCR and sequencing and the obvious presence of a barcoding gap. Results of BLAST 1, nearest distance and neighbor-joining tree methods showed that barcode ITS2 could successfully identify all the texted samples. The secondary structures of the ITS2 region provided another dimensionality for species identification. Two-dimensional images were obtained for better and easier identification. Previous studies on DNA barcoding concentrated more on the same family, genus, or species. However, an ideal barcode should be variable enough to identify closely related species. Meanwhile, the barcodes should also be conservative in identifying distantly related species. This study highlights the application of barcode ITS2 in solving practical problems in the distantly related local alternatives of medical plants.